2017
DOI: 10.1590/s1806-92902017000600004
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of corn silage from intensive dairy farms in Brazil

Abstract: -The objective of this research was to characterize the nutritive value of corn silage made on intensive dairy farms and demonstrate the nutritional variations between silages located at the top and at the center of a bunker silo. Thirty-two dairy farms were visited in four Brazilian states. One corn bunker silo of each farm was chosen and samples were collected from the top and center parts. The nutritive value, fermentation end-products, and microbial counts were assessed. The predicted milk was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 29 publications
2
13
0
4
Order By: Relevance
“…Maize and soybean are the most common grain crops in Brazil. Maize is the most used forage crop worldwide due to its many advantages such as high dry matter yield, high energy content, consistent-palatable feed, reduced total feed cost, rapid harvest and storability potential (Lempp et al, 2000), although, its low crude protein content may play a limitation on its use (Lempp et al, 2000;Evangelista et al, 2005;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Maize and soybean are the most common grain crops in Brazil. Maize is the most used forage crop worldwide due to its many advantages such as high dry matter yield, high energy content, consistent-palatable feed, reduced total feed cost, rapid harvest and storability potential (Lempp et al, 2000), although, its low crude protein content may play a limitation on its use (Lempp et al, 2000;Evangelista et al, 2005;Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature [19] [34] [35] reports CP of silage of Napier grass as ranging from 7.01% -13.9%. Equally, Mediksa et al [34], De Oliveira et al [36] and Wei et al [37] observed that maize silage had CP in the range of 6.1% -9.7% and ME of up to 17.6 MJ/kg. Our findings of 13.7% CP for Napier grass and 9.38% CP for maize and the energy values of 9.80 and 9.60 MJ/kg, respectively, corroborate results in the earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…Despite major relevance, there is a lack of information about the mineral composition of the corn silage produced in Brazil, with most studies focusing on biochemical aspects (Costa et al, 2017;De Oliveira et al, 2017;Pontes et al, 2018), dry matter production, and presence of mycotoxins (Schmidt et al, 2015). Besides, nutrient concentrations of corn plant results from technological level applied by the producer and breeding evolution (Ferreira et al, 2014;Woli et al, 2019), suggesting a need to constantly update reference values.…”
Section: Introductionmentioning
confidence: 99%
“…They analyzed 327 samples from five Brazilian dairy-producing regions and found highly variable ash content (averaging 3.3% of DM) from 1.1 (minimum) to 10.9% of DM (maximum). De Oliveira et al (2017) analyzed thirty-two corn silage samples from Minas Gerais, São Paulo, Paraná, and Rio Grande do Sul states and concluded that corn silage produced on intensive dairy farms in Brazil had satisfactory nutritive value for tropical climate conditions, but had greater content of neutral detergent fiber and lower digestibility compared with silages from the United States. Schmidt et al (2015) reported highly variable chemical composition for all evaluated parameters.…”
mentioning
confidence: 99%